(untitled) (One Health & Risk Management, 2022)
Introduction. It is known that excessive formation of hydrogen peroxide in the microbial cultures under the action of chemical compounds with antibacterial effects is the first stage in the formation of oxidative stress. Thus, it became appropriate to conduct a study that would make it possible to control the level of oxidative stress induced by chemical compounds in cultures of pathogenic microorganisms. Material and methods. The objects of the in vitro study were Cu(II) coordination compounds; Co(II), Zn(II) and aromatic propenones synthesized a t the Department of Inorganic Chemistry of the State University of Moldova. Antimicrobial activity was tested on 5 reference strains. The level of oxidative stress was controlled using the hydrogen peroxide test, and the level of lipid peroxidation was determined indirectly by monitoring the product of peroxidation, namely the malondialdehyde. Results. Under the action of new chemical compounds with antimicrobial properties on reference cultures of Staphylococcus aureus ATCC 25923, Bacillus cereus ГИСК 8035, Escherichia coli ATCC 25922, Shigella sonnei ATCC 25931 and Salmonella enterica (Salmonella abony ГИСК 03/03y) in cultures that create a state of oxidative stress, confirmed by the accumulation of hydrogen peroxide and lipid peroxidation products. Conclusions. Thus, the process of lipid peroxidation, which follows the pattern of chain reactions, is one of the reactions that lead to the death of cell culture. The level of hydrogen peroxide formed under the action of the tested compounds was also monitored.